Les défis des communautés côtières pour rehausser la résilience et leur capacité à faire face aux intempéries climatiques - Antonia-Djèmila Bousbaine; Christopher Bryant (VertigO)
The purpose of this article is to present the challenges coastal communities face in increasing their level of resilience and capacity to adapt to climatic disturbances. The emphasis is on the need to integrate these two elements in a holistic process of reflection and long-term strategic planning. This is necessary to avoid the marginalization of the issue of climate change and variability (CVC) compared to other issues facing these communities (e.g. the maintenance and development of employment and services for the population). We use the concepts of strategic planning for and by the community, which involves the mobilization and participation of all legitimate segments of interest in the community in all phases of strategic planning : building a future vision, the identification of strategic orientations (including potentially one focused on resilience and adaptive capacity) ; the identification of the types of possible and desirable actions in this type of orientation …). We make reference to coastal zones in Quebec, New Brunswick and Western Europe. The results demonstrate. the importance first of appropriating the issue of CVC as a recurrent phenomenon and the mobilization of all segments of interest in a community regardless of whether certain segments are themselves directly affected by this phenomenon or not. In conclusion, we emphasize the importance of effective communication at each step and of building a culture of community solidarity which can be in itself a strategic orientation.